Konversi Agama dari Hindu ke Islam Pada Masyarakat Banyuwangi: Analisis Sejarah Kritis - Ali Mursyid Azisi; M. Yusuf (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2021)
Conversion of Religion from Hinduism to Islam in Banyuwangi: Critical Historical Analysis. The purpose of writing this article is to describe the situation and condition of the previous Blambangan kingdom. Also, try to explain how Islam entered and developed in Banyuwangi. Hinduism in the land of Banyuwangi can not be separated from several kingdoms in the archipelago. With the establishment of Islamic education such as pesantren whose influence is very strong at the eastern end of the island of Java, then the marriage line, coupled with the influence of power, Islam can flourish amid the majority of Hindu communities.